Genome sequence of Ralstonia syzygii subsp. celebesensis, the causal agent of banana blood disease on Musa balbisiana cultivar Kepok in bali, Indonesia - Ady Bayu Prakoso; Siti Subandiyah; Intan Berlian; Tri Joko; Fenny Martha Dwivany; Yudo Prasetyo; Ketut Wikantika; Tri Muji Susantoro (BMC Research Notes)
Abstract Objectives Blood Disease of Banana brought on by Ralstonia syzygii subsp. celebesensis (Rsc) results in yield losses in Indonesia up to 90%. Among the symptoms are wilting, vascular staining, fruit rot, and plant death. Pathogen travels via contaminated tools, water runoff, pests, and pollinators. Originally reported in South Sulawesi, it now affects all of the main Indonesian islands as well as Malaysia. Though its influence is known, understanding of Rsc pathogenesis is less than that of Ralstonia solanacearum. This study investigates the different genome of Rsc isolate from Bali, geographically separated by the Wallace Line, and compares them to published genomes from Yogyakarta. Data description The data presented were obtained as a byproduct of a broader genomic survey on Rsc diversity. The genome structure and G + C content analysis of Rsc, which was isolated from Musa balbisiana cultivar Kepok in Bali, is included in the draft genome sequence. The genome’s size, coding sequence patterns, and functional annotations were assessed after being assembled from scratch. Genome analysis pipeline was used to process each sequencing data separately using protocols created for Oxford Nanopore sequencing outputs. Comparative analysis with the Yogyakarta isolate highlights molecular variations likely influenced by geographic isolation across the Wallace Line.